“Opuntia dillenii” – An Interesting and Promising Cactaceae Taxon - Böhm, Hartmut (Journal of the Professional Association for Cactus Development, 2008)
The origin, distribution, and taxonomy of Opuntia dillenii are reported and the various investigations are reviewed, which have been carried out with this cactus during the last 25 years. Biological and chemical characterization revealed properties typical of succulent plants and betalains as most noticeable constituents accompanied by flavonoids, other phenolics, ascorbic acid, and certain minerals as significant compounds. Although practically not cultivated, O. dillenii has been used in several directions despite its stout spines on old cladodes. The fruits are consumed or provide colouring. Generative and vegetative parts of the cactus have had a lasting position in folk medicine and their effects could partly be proved in scientific experiments. In face of its valuable characteristics, O. dillenii is recommended as a promising candidate of programmes directed to the development of Opuntia species into crop plants.